2007
DOI: 10.1371/journal.pbio.0050243
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genome-Wide Dissection of the Two Rules of Speciation in Drosophila

Abstract: Postzygotic reproductive isolation is characterized by two striking empirical patterns. The first is Haldane's rule—the preferential inviability or sterility of species hybrids of the heterogametic (XY) sex. The second is the so-called large X effect—substitution of one species's X chromosome for another's has a disproportionately large effect on hybrid fitness compared to similar substitution of an autosome. Although the first rule has been well-established, the second rule remains controversial. Here, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
341
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(362 citation statements)
references
References 78 publications
16
341
4
1
Order By: Relevance
“…When two diverged populations hybridize, the drivers may escape the control of the suppressors and cause male sterility. Orr et al (2006) found that the same genes influence hybrid sex ratios and hybrid sterility in crosses between two Drosophila species, although Masly and Presgraves (2007) found no supporting evidence in another Drosophila study.…”
Section: Evolution Of Genetic Incompatibilitymentioning
confidence: 91%
See 2 more Smart Citations
“…When two diverged populations hybridize, the drivers may escape the control of the suppressors and cause male sterility. Orr et al (2006) found that the same genes influence hybrid sex ratios and hybrid sterility in crosses between two Drosophila species, although Masly and Presgraves (2007) found no supporting evidence in another Drosophila study.…”
Section: Evolution Of Genetic Incompatibilitymentioning
confidence: 91%
“…Studies of disproportionate X/Z effects that account for recessivity of hybrid dysfunction remain few and only for maleheterogametic taxa, but appear to support a large X effect for sterility (Table 1). True et al (1996), Tao et al (2003) and Masly and Presgraves (2007) have provided convincing evidence that male sterility factors in crosses between Drosophila simulans, D. mauritiana and D. sechellia occur at a higher density on the X chromosome than on autosomes and at a much higher density than female sterility factors, supporting faster male evolution. Their results also reveal an excess of recessive incompatibilities, supporting the dominance theory, but leave open the question of whether faster-X evolution is involved.…”
Section: Evolution Of Genetic Incompatibilitymentioning
confidence: 97%
See 1 more Smart Citation
“…The second rule is named the large X-effect, and is based on observation that the X (or Z) chromosome has a disproportionately high impact on hybrid fitness compared to autosomes. This has been shown, in Drosophila, to be due to a higher density of male sterility factors in the X chromosome 6,7 .…”
mentioning
confidence: 96%
“…The rate of this process is again dependent on the amount of degeneracy between sex chromosomes. Here I separate the large X-effect from the effects of dominance, where a large X-effect is caused by a higher density of incompatibilities accumulating on the X (Z) chromosome 6,7 , and not due to the fact that hemizygosity exposes incompatibilities in this chromosome (dominance theory). Of course, if the incompatibilities that stem from both faster X and/or faster-heterogametic-sex (which lead to the large X-effect) are on average partially recessive, we would observe an exaggerated pattern due to the combination of the large X-effect and the dominance theory 20 .…”
mentioning
confidence: 99%